Analisis Kapasitas dan Kerentanan Perempuan Pekerja Rumput Laut Perbatasan Selama Krisis Pandemi Covid-19 - Miladiyatu Tsania Zulfa; Ambar Widaningrum (Jurnal Inada: Kajian Perempuan Indonesia di Daerah Tertinggal, Terdepan, dan Terluar, 2023)
The Covid-19 pandemic crisis places women in a vulnerable position. Female seaweed workers or mabbetang at Pantai Indah Pulau Sebatik are one of the groups that were affected by it. Sebatik Island, as part of the Indonesia-Malaysia border, has sea potential, mainly seaweed cultivation. This study aims to discuss the capacities and vulnerabilities of mabbetang at the Indonesian border in dealing with the Covid-19 pandemic crisis. The research method uses descriptive qualitative using capacity and vulnerability analysis framework/CVA. Primary data collection was obtained through Focus Group Discussion (FGD) and observations with mabbetang, as well as secondary data through literature reviews. The results of the study show that mabbetang have vulnerabilities and capacities (physical, social, and motivational aspects) in carrying out activities, especially during times of crisis. The vulnerabilities faced include limited access to health, infrastructure, capital, and double burdens. However, mabbetang women also have capacities including the strength of kinship social relations, emergency savings, and work flexibility. The research uses the help of NVivo software with project map visualization to produce strategic implications for capacity building and reducing vulnerability which is expected to contribute to policymakers in taking policy steps to empower women and seaweed cultivation on the Indonesian border coast.